Glaucoma and CNS. Comparison of fMRI results in high tension and normal tension glaucoma - Lestak, Jan; Tintera, Jaroslav; Svata, Zuzana; Ettler, Lukas; Rozsival, Pavel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2014)
AIM: The objective of our work was to determine whether there is a difference in fMRI activation between patients with high tension glaucoma (HTG) and those with normal tension glaucoma (NTG). METHOD: The sample consisted of eight patients with different stages of high tension glaucoma (3 females aged 41-65 and 5 males aged 40-73 years) and eight patients, also with different stages of normal tension glaucoma (6 females aged 53-70 and 2 males aged 40-52 years). The control group consisted of eight healthy subjects (3 females aged 23-46 and 5 males aged 23-65 years). All underwent complete ophthalmological examination, including visual field, colour vision, and electrophysiological functions. The results were compared with fMRI images after stimulation with black/white (BW) and blue/yellow (BY) checkerboard and then statistically processed. RESULTS: The authors analyzed the results of published studies on high tension versus normal tension glaucoma in the images obtained by fMRI. They concluded on the basis of electrophysiological examinations that in high tension glaucoma, damage of the whole visual pathway occurs, starting from retinal ganglion cells up to the visual cortex. In normal tension glaucoma the response of ganglion cells is relatively normal. The pathology is found mainly in the visual pathway. For this reason, the authors carried out fMRI examinations in high tension glaucoma patients and patients with normal tension glaucoma. They found that advancing stages of high tension glaucoma cause progression of fMRI activity decrease. These relations were not observed in normal tension glaucoma cases. Similarly, in high tension glaucoma on fMRI examination to yellow/blue stimuli, the fMRI activity decrease was found to be greater than that to black/white stimulation. No similar effect was observed in normal tension glaucoma. CONCLUSION: Normal tension glaucoma is, from the etiopathogenetical view, a different disease than high tension glaucoma.
Keywords: Magnetic Resonance Imaging; glaukom; magnetická rezonanční tomografie; Humans; zraková pole; Color Vision; lidé středního věku; zrakové korové centrum; Female; Aged; mladý dospělý; dospělí; Glaucoma; senioři; lidé; Functional Neuroimaging; Photic Stimulation; nitrooční tlak; světelná stimulace; Adult; ženské pohlaví; Male; Middle Aged; vidění barevné; Young Adult; Visual Fields; funkční zobrazování neurálních procesů; mužské pohlaví; Visual Cortex; Intraocular Pressure